2012
DOI: 10.1002/jssc.201100859
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of dihydroxybenzene positional isomers by capillary electrochromatography using gold nanoparticles as stationary phase

Abstract: The paper describes the enhanced separation of o-, m-, p-dihydroxybenzene by capillary electrochromatography (CEC) using gold nanoparticles (AuNPs) as stationary phase. The effect of the AuNPs concentration upon separation was investigated. The experimental parameters, including separation voltage, pH, and concentration of running buffer, were optimized. Under the optimum conditions, a good resolution of three dihydroxybenzene isomers was obtained within 15 min in a 50 cm effective length capillary modified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A). It had been reported that using modified GNPs for enantioselective recognition of chiral analytes, such as dansyl‐ d and l ‐norvaline, and in the work of He , GNPs were used as a stationary phase for separation of dihydroxybenzene positional isomers by CEC. All these above reports illustrated GNPs may possess some structural recognition capability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A). It had been reported that using modified GNPs for enantioselective recognition of chiral analytes, such as dansyl‐ d and l ‐norvaline, and in the work of He , GNPs were used as a stationary phase for separation of dihydroxybenzene positional isomers by CEC. All these above reports illustrated GNPs may possess some structural recognition capability.…”
Section: Resultsmentioning
confidence: 99%
“…As a pseudo‐stationary phase or stabilized on modified fused‐silica capillary, GNPs can separate biomolecules , neutral steroid drugs , and polycyclic aromatic hydrocarbons . GNPs can also be used as novel stationary phases providing high separation efficiencies for a variety of analytes in various separation systems , including GC and HPLC .…”
Section: Introductionmentioning
confidence: 99%
“…An enzyme–antibody dual labeled AuNPs enhancing chemiluminescence (CL) strategy was developed for highly sensitive CE‐CL‐immunoassay of prostate‐specific antigen by Zhao's research group. They reported that the use of horseradish peroxidedase and antiprostate‐specific antigen–antibody labelled AuNPs complex as a marker can significantly enhance the CL signals, thus this method offers many advantages including high separation efficiency, simple operation, and low sample consumption .…”
Section: Gold Npsmentioning
confidence: 99%
“…As already mentioned, the use of new nanomaterials also offers higher selectivity, even more as a result of the possibility of post‐attaching a large number of functionalities in the SP containing NPs (see Table ). In the case of AuNPs, although they have also been directly used as bare NPs , it must be taken into account their facility to be functionalized. As an example, You et al.…”
Section: Nanomaterials Applications In Capillary Electrochromatographymentioning
confidence: 99%